Third generation biofuels: Cultivation methods and technologies for processing of microalgal biofuels - Milica Preradović; Saša Papuga (Zaštita Materijala)
Energy production from biomass is gaining a lot of attention. Algal oil (microand macroalgae) can be used for biofuel production. Biofuels from this type of feedstock are called third generation biofuels or advanced biofuels. Focus of this paper is on the microalgal biofuels and on the available process technologies. Very important advantage of microalgal biofuels is that microalgae can be cultivated on any type of land, with the possibility of using wastewater streams. Microalgae can be cultivated in open systems, so called "raceway ponds" or in closed systems - photobioreactors: flat panel photobioreactors, horizontal tubular, vertical tubular photobioreactors with or without airlift. Also, basic information on cultivation conditions (photoautotrophic, heterotrophic, mixotrophic and photoheterotrophic) are presented. Available technologies for microalgal biofuels production are: transesterification, fermentation, pyrolysis, hydrothermal liquefaction, anaerobic digestion and biomass to liquids (BtL). Additionally, basic information on life cycle assessment of microalgae cultivation and CO2 sequestration potential is given in the final chapter of this work.